Ultrasound Evaluation of Biliary Obstruction in Chaoprayayomraj Hospital, Suphan Buri - Jangsrisuk, Jongdee (Journal of Health Science of Thailand, 2018)
A prospective study on the ability of ultrasound to accurately evaluate the site and cause of biliary obstruction compared with the postoperative diagnoses was carried out. It revealed 90 surgically proven cases entered into this series, in whom the sensitivity, specificity, and accuracy of ultrasound evaluation of the site of biliary obstruction were 98.8 percent, 85.7 percent and 97.8 percent respectively; of the cause of biliary obstruction were 97.6 percent, 85.7 percent and 96.7 percent respectively, respectively, which were relatively high in comparison with multiple previously published series. So this study could support that in Chaoprayayomraj hospital, the screening role of ultrasound in differentiation between obstructive and nonobstructive biliary tract diseases could be extended to gain information of the site and cause of biliary obstruction, of the extension and operability of the tumor, to assess the presence of both ascites and metastatic foci in the liver thus aiding in the staging of neoplastic disease. It also could accurately guide further therapeutic maneuver, which were sufficient to evaluate patients prior to surgery, while cholangiography (PCT and ERCP) and computed tomography (CT) should probably be used only when satisfactory ultrasound examination could not be obtained, in order to avoid the risk of the potentially hazardous complications of the procedures, contrast media administration and radiation; to reduce the high cost and the difficulty in referring the patients. Review of literatures concerning ultrasound evaluation of biliary obstruction were performed. Practical points of making ultrasound evaluation of biliary obstruction were discussed as :- technique of ultrasonographic examination, anatomical relationships of biliary tract, criteria used in ultrasound diagnosis of biliary obstruction, determination and interpretation of its site and cause.